Identification and Characterization of USP7 Targets in Cancer Cells. Issue 1 (December 2018) - Georges, Anna; Marcon, Edyta; Greenblatt, Jack; Frappier, Lori
Abstract The ubiquitin specific protease, USP7, regulates multiple cellular pathways relevant for cancer through its ability to bind and sometimes stabilize specific target proteins through deubiquitylation. To gain a more complete profile of USP7 interactions in cancer cells, we performed affinity purification coupled to mass spectrometry to identify USP7 binding targets in gastric carcinoma cells. This confirmed reported associations of USP7 with USP11, PPM1G phosphatase and TRIP12 E3 ubiquitin ligase as well as identifying novel interactions with two DEAD/DEAH-box RNA helicases, DDX24 and DHX40. Using USP7 binding pocket mutants, we show that USP11, PPM1G, TRIP12 and DDX24 bind USP7 through its TRAF domain binding pocket, while DHX40 interacts with USP7 through a distinct binding pocket in the Ubl2 domain. P/A/ExxS motifs in USP11 and DDX24 that are critical for USP7 binding were also identified. Modulation of USP7 expression levels and inhibition of USP7 catalytic activity in multiple cells lines showed that USP7 consistently stabilizes DDX24, DHX40 and TRIP12 dependent on its catalytic activity, while USP11 and PPM1G levels were not consistently affected. Our study better defines the mechanisms of USP7 interaction with known targets and identifies DDX24 and DHX40 as new targets that are specifically bound and regulated by USP7.